Islam as critique Sayyid Ahmad Khan and the challenge of modernity - Hussain, Khurram (London New York Oxford New Delhi Sydney Bloomsbury Academic, 2021)
Prologue -- Introduction -- 1. The language of reform -- 2. Modernism and humanism -- 3. The meaning and end of time -- 4. The viva activa -- 5. Knowledge and wisdom -- Epilogue: Can the Muslim speak? -- Notes -- Bibliography -- Index.
Literaturverzeichnis: Seite 194-203. - Index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Aḥmad K̲h̲ān̲, Sayyid -- Sir -- 1817-1898 -- Criticism and interpretation; Islamic Modernism; East and West; Aḥmad K̲h̲ān̲, Sayyid; International Relations; Islamic countries; Western countries; Criticism, interpretation, etc; Islamic countries -- Relations -- Western countries; Western countries -- Relations -- Islamic countries